A Novel Four-Dimensional Energy-Saving and Emission-Reduction System and Its Linear Feedback Control - Minggang Wang; Hua Xu (Journal of Applied Mathematics)
This paper reports a new four-dimensional energy-saving and emission-reduction chaotic system. The system is obtained in accordance with the complicated relationship between energy saving and emission reduction, carbon emission, economic growth, and new energy development. The dynamics behavior of the system will be analyzed by means of Lyapunov exponents and equilibrium points. Linear feedback control methods are used to suppress chaos to unstable equilibrium. Numerical simulations are presented to show these results.